اتجاهات طلاب الجامعة نحو التلعيب في تعلم الاتسّاق في اللغة العربية - Jalil, Siti Zubaidah; Mohd Ismath, Nurul Hanilah (Kolej Universiti Islam Antarabangsa Selangor (KUIS), 2022)
This research seeks to know the students' attitudes towards gamification in learning arabic cohesive devices in the Arabic language, and looking at the level of students' enjoyment towards gamification. Gamification refers to the application of game mechanics in non-game environments with the aim of enhancing the enacted processes and the experience of its participants. The researcher used the quantitative descriptive approach and distributed the questionnaire using a survey method to 50 first- and second-year students from the University of Islamic Sciences Malaysia. The questionnaire was distributed to the sample members through Google Form. Then, the researcher collected the data and entered SPSS to analyze it and extract the arithmetic means and standard deviations. From the results of the research, Gamification has a positive effect on students in higher education, especially in learning a foreign language, and through it, the process of learning arabic cohesive devices in the Arabic language takes place with all interaction and enjoyment, which increases the students' interest for learning. Finally, gamification provides the opportunity for learners to engage with content in an effective, informal learning environment.